Situation Report: Romania, 26 October 1962 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Reaction to Quarantine against Cuba (continued) Yugoslav Industry Secretary for Romania Greek Industry Secretary for Romania Greek-Romanian Indemnity to Be Resumed Romanian-Bulgarian Technical-Scientific Cooperation